The effect of anxiety induction on the regional uptake of 99mTc-exametazime in simple phobia as shown by single photon emission tomography (SPET). - O'Carroll, R; Moffoot, A; Van Beck, M; Dougall, N; Murray, C; Ebmeier, K; Goodwin, G (1993)
Ten patients suffering from DSM-III-R simple phobia were studied under two conditions: (a) while listening to a 4 min relaxation tape, and (b) while listening to a 4 min audio tape describing exposure to the phobic stimulus. During each condition, subjects were injected with 99mTc-Exametazime, a marker of regional cerebral blood flow. Subjective and psychophysiological measures indicated a marked effect of the anxiety induction procedure. Ratio analysis of the SPET data revealed reductions in tracer uptake largely confined to posterior cerebral regions bilaterally. Analysis of brain regions of interest normalised to the whole brain slice showed reductions confined to right temporal/occipital regions. In general there was no clear association between subjective and physiological variables and changes in regional uptake of tracer as a consequence of the anxiety induction procedure. The changes in tracer uptake were dissimilar to those previously reported for other cognitive activation paradigms, providing some reassurance that those functional brain changes were not artefacts of non-specific changes in state anxiety. These posterior brain changes may reflect alterations in activation of the GABA/benzodiazepine complex.